Pengaruh Sistem Informasi Akuntansi Manajemen dan Pemanfaatan Teknologi Informasi terhadap Kinerja Manajerial: Studi Empiris pada Hotel Se-Kabupaten Buleleng - Winata, I Gede Pramudja Harja Winata; Ni Wayan Yulianita Dewi (Universitas Pendidikan Ganesha, 2024)
This research aims to examine the influence of Management Accounting Information Systems and the Use of Information Technology on Managerial Performance (Empirical Study in Hotels in Buleleng Regency). This research is quantitative research using primary data obtained through data collection techniques using questionnaires. The population in this study was 153 hotels in Buleleng Regency which were then selected using Purposive Sampling criteria to adapt to the phenomenon that occurred in this research, namely the researcher chose 3 star hotels and below in Buleleng District and Gerokgak District because the hotels in these districts had the most bankruptcies or closures. while so the final sample in this study was 64 hotels. The data analysis techniques used in this research consist of validity tests, reliability tests, loading factors, outer models (convergent validity, discriminant validity, composite reliability) and inner models (R-Square, path coefficients and their significance). The results obtained are that the management accounting information system has a positive effect on managerial performance, and information technology has a positive effect on managerial performance. For the coefficient of determination test results, it is known that the independent variable in this study is able to explain the dependent variable Managerial Performance by 84.5% while the rest is explained by other variables that are not yet included in the model.